Gateway to Recovery: A Comparative Analysis of Stroke Patients’ Experiences of Change and Learning in Norway and Denmark - Pallesen, Hanne; Aadal, Lene; Moe, Siri; Arntzen, Cathrine (Rehabilitation Research and Practice, 2019)
Source at https://doi.org/10.1155/2019/1726964. Objectives : The recovery process is reported by stroke survivors to be a change process fraught with crises and hazard. Interaction with health professionals and others may play a central role in establishing renewed control over life. Research Questions : (1) How do patients handle and overcome experienced changes after stroke? (2) How do they experience the support to handle these changes during the first year after stroke? (3) How do the similarities and differences transpire in Danish and Norwegian contexts? Methodology : A qualitative method was chosen. Six patients from Denmark and five patients from Norway (aged 25-66) were followed up until one year after stroke, by way of individual interviews. The data were analyzed (using NVivo 11) by means of phenomenological analysis. Findings : The participants described four main issues in the recovery process that impacted the experienced changes: (i) strategies and personal factors that promote motivation, (ii) the involvement of family, social network, and peers, (iii) professionals’ support, and (iv) social structures that limit the recovery process. There was a diversity of professional support and some interesting variations in findings about factors that affected recovery and the ability to manage a new life situation between Central Denmark and Northern Norway. Both Norwegian and Danish participants experienced positive changes and progress on the bodily level, as well as in terms of activity and participation. Furthermore, they learned how to overcome limitations, especially in bodily functions and daily activities at home. Unfortunately, progress or support related to psychosocial rehabilitation was almost absent in the Norwegian data.